THE EXISTENCE OF SINGA DANGDUT AS A FORM OF CULTURAL REPRODUCTION OF SISINGAAN ART IN SUBANG REGENCY - Fauzi, Lesa; Prasetyo, Kuncoro Bayu (Program Studi Sosiologi Universitas Malikussaleh, 2024)
This research article aims to analyze the cultural reproduction process that transformed the traditional art of Subang Regency, namely Sisingaan, into Singa Dangdut in the Lodaya Putra Group. It also aims to identify the factors that caused the cultural reproduction of this art. Sisingaan is a characteristic of Subang Regency that has undergone changes and evolved into a popular art form known as Singa Dangdut. For this research, a qualitative approach was used, which involved observation, interviews, and document studies. The data sources used were primary data obtained directly from the field and interviews, as well as secondary data in the form of documents obtained from the field. Data validity was tested using the triangulation method. The research findings show that the reproduction of Sisingaan into Singa Dangdut occurred through five aspects that underwent changes and innovations, including (a) the appearance of the lion puppet, (b) accompanying musical instruments, (c) choreography, (d) performance, and (e) costumes. The factors that caused this reproduction were both internal and external to the art group and society. The internal factors were the changing musical taste of the Lodaya Putra Group members from traditional songs to Dangdut music. This was because the current members of the Lodaya Putra Group are dominated by young people who tend to prefer popular music over traditional music. The external factors were the process of traditional cultural acculturation with modern culture and market demands.